2017
DOI: 10.1007/978-3-319-58068-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Actively Learning to Rank Semantic Associations for Personalized Contextual Exploration of Knowledge Graphs

Abstract: Knowledge Graphs (KG) provide useful abstractions to represent large amount of relations that occur between entities of different types. Chains of such relations represented by semantic associations reveal connections between entities that may be interesting, and possibly unknown, to a user, thus resulting valuable for her to get insights into a given topic. For example, in contextual exploration of KGs, we may want to let a user explore a set of semantic associations that are deemed to be more interesting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A graph-based recommendation methodology based on a personalised PageRank algorithm has been proposed in [50]. The approach in [51] allows the user to rate semantic associations represented as chains of relations to reveal interesting and unknown connections between entities for personalised recommendations.…”
Section: Text-based Semantic Data Browsersmentioning
confidence: 99%
“…A graph-based recommendation methodology based on a personalised PageRank algorithm has been proposed in [50]. The approach in [51] allows the user to rate semantic associations represented as chains of relations to reveal interesting and unknown connections between entities for personalised recommendations.…”
Section: Text-based Semantic Data Browsersmentioning
confidence: 99%
“…Bianchi et al [41] focus on the problem of finding the most "interesting" semantic associations by defining a ranking function, which can take into account user preferences. The approach starts from a small sample of semantic associations that are rated by the user and then use it to iteratively learn a personalized ranking function.…”
Section: Discovering Semantic Associationsmentioning
confidence: 99%
“…Semantic association ranking is to rank the semantic relationship for a given entity pair. RankSVM [10] and actively learning [2] has been proposed for personalized ranking and minimizing labels collected from the user. None of those entity summarization and semantic association work, however, incorporate a context as part of the ranking consideration.…”
Section: Related Workmentioning
confidence: 99%
“…We observed that often the same facts were chosen but in different orders. So we asked raters to assign an informative level to each fact using one of the four ratings: Crticial(4), Informative(3), Uninformative (2) and Unrelated (1). Average scores over top-k positions are shown in Figure 9 with standard deviation ommited for clarity.…”
Section: Table Synthesismentioning
confidence: 99%